Enhancing R410A blend separation by using ionic liquids: From UNIFAC model extension, solvent design to molecular dynamics simulation. (15th June 2023) - Qin, Hao; Xie, Kunchi; Li, Linmin; Cheng, Jie; Song, Zhen
Highlights: UNIFAC-IL model is extended to cover R410A refrigerant blend (R-32 and R-125). CAILD is performed to rationally design ILs for separating R410A blend. MD simulations are conducted to elucidate the rationality of CAILD results. Abstract: The selective separation of refrigerants could facilitate their reclamation and reduce emissions of hydrofluorocarbons (HFC) with high global warming potential. R410A, a near azeotropic mixture comprising equimass difluoromethane (R-32) and pentafluoroethane (R-125), is required to be phased out and shortly replaced by more efficient and sustainable refrigerants. Under this background, the recovery of R-32 and R-125 by using ionic liquids (ILs) as the solvent is considered as a promising approach. In this work, the rational selection of ILs for enhancing the R410A separation is presented. To this end, 873 refrigerant-in-IL solubility data (573 for R-32, 300 for R-125) are firstly adopted for the extension of the UNIFAC-IL model to cover the R410A system. With the obtained UNIFAC-IL model, a computer-aided IL design (CAILD) task is cast as a mixed-integer nonlinear programming (MINLP) problem, which is solved to identify three top-ranked ILs. Following that, molecular dynamics (MD) simulations of the selected IL-refrigerant systems are conducted, which well elucidate the reliability of the CAILD results.